Development and differentiation - Katten, Steven; CRM Productions (Del Mar, Calif. : CRM/McGraw-Hill Films, 1974)
Deals with the mechanism by which an embryo develops into a highly organized conglomerate of cells. Uses animation to show the functioning of cells, and explains the roles of DNA and cytoplasm.
Keywords: Embryology; Cell differentiation